Solar energy: A promising renewable source for meeting energy demand in Indian agriculture applications. (February 2023) - Kumar, Ch. Mohan Sai; Singh, Suman; Gupta, Manglesh Kumar; Nimdeo, Yogesh M.; Raushan, Ravi; Deorankar, Ankit V.; Kumar, T.M. Ananda; Rout, Prasant Kumar; Chanotiya, C.S.; Pakhale, Vinod D.; Nannaware, Ashween Deepak
Graphical abstract: Graphical representation of Solar Energy benefits and its applications. Highlights: Solar energy emerged as a reliable and environmentally clean technology. The Indian government has proposed a large-scale installation of solar panels. Exploration of solar energy reduces global warming concerns. India's market and society are integrating solar energy. Solar energy application in agriculture boosts the economy of the country. Abstract: India is the fifth economic power in the World, and 20% of its GDP is contributed by the agriculture and allied sector. The agricultural sector entails various activities involving land preparation, irrigation, crop growth, harvesting, food processing, etc. For meeting the current agricultural energy demand in India, renewable solar energy has come up as a prime energy source that can reduce the farmer's dependency on the use of conventional energy sources. The regular usage of fossil fuels leads to its depletion and releases considerable CO2 into the atmosphere. It is estimated that 4600 GW of installed solar energy systems would circumvent about 4 gigatons of CO2 emissions yearly by 2050. As a result, solar energy has been recognized as one of the most promising renewable alternatives to create heat and electricity via solar technologies for agriculture as well as various industrial processes. This review focuses on the status, importance, availability, and applications of solar energy technologies in numerous agricultural operations that are currently taking place all over India. This review also highlights the socioeconomic importance, environmental impact, economic analysis, SWOT analysis, and future technological potential of solar energy uses along with some limitations to its extensive utilization in India.